STUDENTS’ PERCEPTION OF DIFFICULTIES IN INDONESIAN-ENGLISH TRANSLATION: A SURVEY STUDY TO THE FIFTH SEMESTER STUDENTS - Siti Muyassaroh (Universitas Negeri Manado, 2022)
This study aims to describe students’ perceived difficulties in doing Indonesian-English translation, factors that caused the perceived difficulties, and strategies to overcome the difficulties. There were 90 students in the English Education Program at UNNES who completed the online questionnaire. From the results of the questionnaire, 10 students who had the highest score of translation difficulties were chosen to be interviewed. The findings revealed that most of the translation difficulties by Nord presented in the questionnaire were perceived by the students. The most perceived difficulties by the students, respectively, were technical, pragmatic, translator-dependent, and text-specific difficulties. While based on the interview with 10 respondents who got the highest score on the questionnaire, those difficulties were caused by some factors. They were lack of knowledge, lack of methodology, lack of motivation, lack of references, and other technical factors. With the same instrument, interview, there are also other findings, namely students’ strategies for overcoming their perceived difficulties. There were five strategies applied by the students, including finding more references; maximizing the use of translation tools; using descriptive equivalent techniques; using literal techniques; and asking friends.